2021
DOI: 10.3390/membranes11030166
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of DMEA-Grafted Anion Exchange Membrane for Adsorptive Discharge of Methyl Orange from Wastewaters

Abstract: This manuscript describes the synthesis of dimethylethanolamine (DMEA)-grafted anion exchange membrane (AEM) by incorporating dimethylethanolamine as ion-exchange content into the polymer matrix via the solution casting method. The synthesis of the DMEA-grafted AEM was demonstrated by Fourier transform infrared (FTIR) spectroscopy. The prepared DMEA-grafted AEM exhibited higher thermal stability, homogeneous morphology, water uptake (WR) of 115%, and an ion exchange capacity (IEC) of 2.70 meq/g. It was used fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 49 publications
0
26
0
Order By: Relevance
“…Solution casting method was used to fabricate the SPEEK/SPPO blended membranes as reported previously [ 36 , 37 , 38 , 39 , 40 , 41 , 42 ]. In a typical procedure, we got homogeneous solution of SPEEK by dissolving its calculated amount into 20 mL of N-Methyl-2-pyrrolidone (NMP).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Solution casting method was used to fabricate the SPEEK/SPPO blended membranes as reported previously [ 36 , 37 , 38 , 39 , 40 , 41 , 42 ]. In a typical procedure, we got homogeneous solution of SPEEK by dissolving its calculated amount into 20 mL of N-Methyl-2-pyrrolidone (NMP).…”
Section: Methodsmentioning
confidence: 99%
“…Wet weight of these membranes was then measured. Water uptake ability was determined by employing the following relationship [ 38 , 46 , 47 ]: where W WET (g) and W DRY (g) are the weights of wet and dry membranes, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…In this work, the solution casting method was utilized for the synthesis of BPPO-based anion exchange membranes as reported in our previous research [ 35 , 43 , 44 , 45 , 46 , 47 ]. At first, 7% (wt %) solution was formed by dissolving 0.7 g (2.6 mmol) of BPPO into N-methyl-2-pyrrolidone (NMP) solvent.…”
Section: Methodsmentioning
confidence: 99%
“…In this work, the solution casting method was utilized for the synthesis of BPPObased anion exchange membranes as reported in our previous research [35,[43][44][45][46][47]. At first, In this paper, the formulation of a sequence of homogeneous anion exchange membranes based on BPPO with varying physico-chemical characteristics has been revealed by altering the amount of triphenylphosphine (shown in Figure 3) through the use of the solution casting method into the polymer matrix.…”
Section: Procedures For Synthesis Of Anion Exchange Membranesmentioning
confidence: 99%
“…Khan et al [2] reported on the synthesis of a dimethylethanolamine-grafted anionexchange membrane by incorporating dimethylethanolamine as the ion-exchange content into the polymer matrix via the solution-casting method. This membrane exhibited a homogeneous morphology, water uptake of 115%, an ion-exchange capacity of 2.70 meq/g, and high thermal stability.…”
mentioning
confidence: 99%